Penyerapan Ion Logam Zn (II) dengan Biji Buah Lengkeng (Euphoria Longan Lour) sebagai Biosorben - Suciandica, Mutiara (RC-INSTITUT, 2019)
One of methods that is often used to absorb heavy metal ions is biosorption. Research has been used on the absorption of Zn + 2 heavy metal ions using longan seeds as biomass batch method. Variations that affect the absorption of heavy metal ions such as pH, concentration, particle size, contact time and stirring speed, from each variation carried out found optimum conditions at pH 5 of 11, 8475 mg / g, 200 ppm concentration, 106 µm particle size, 60 minutes of contact time at 150 rpm has a maximum absorption capacity of 2.8868 mg / g. Interaction between the adsorbent and the adsorbate was determined using the langmuir and freadlich equations in the research of this time to have aiquired balance that fulfilled langmuir equation, while the characterization was determined using FTIR.   Keywords: heavy metal Zn+2, euphoria longan lour, batch.